(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
ينظر هذا البحث إلى الأدب الشعبي على أنه أدب القبول، وأدب الرفض في الآن نفسه، ويهتم بدراسة البعد الدرامي في أغاني ترقيص الأطفال في الأدب العربي القديم؛ ذلك لأن الرقص ارتبط بالغناء منذ القدم؛ إذ تعد أغاني الترقيص هذه مثالاً لاجتماعهما، فقد نظمت على وفق إيقاع راقص، والحركة أساس الدراما، ومن هنا تنجم العلاقة بين أغاني ترقيص الأطفال والدراما. ويدرس البحث هذا الموضوع على وفق الآلية الآتية: -تحديد المصطلحات التي ستكون محور البحث -المحتوى الدرامي في هذه الأغاني -خصائص الخطاب الدرامي وينطلق من فكرة أن لكل خطاب خطاباً مضاداً، ولكل فكر فكراً مضاداً. فما العلاقة بين الصوت والفكر من جهة، وما التفاعلات الخطابية الدرامية في هذه الأغاني من جهة أخرى؟ This paper views folk literature as one of acceptability and of rejection at the same time. It is also concerned with the dramatic dimension of the art of lullaby in classical Arabic literature because choreography was associated with the art of singing all along, and lullabies are considered an example of their combination, because they were arranged in accordance with a choreographic effect. And, since movement is the basis of drama, there follows the relation between lullabies and drama. This paper examines this subject in terms of the following mechanism: -Identifying the terms which will form the pivot of this paper. - The dramatic content of these lullabies - The characteristics of dramatic discourse This study stems from the idea that every discourse has a counter- discourse, and that every thought has its counter–thought. Thus, what is the relation between voice and thought on the one hand, and what are the dramatic discursive interactions in these lullabies on the other?